Perceiving Natural Speed in Natural Movies. (July 2019) - Kobayashi, Mikako; Motoyoshi, Isamu
The visual system uses the physical laws of nature as constraints for perceiving objects and events. Images violating natural laws would therefore tend to be perceived as unnatural. To understand vision's implicit knowledge of natural speed in the real world, we examined visual tolerance to artificial speed deviations in 22 natural movies. For most movies, perception could tolerate deviations from original speed by as much as a factor 2×. However, for movies including human body movements or falling objects, perception only tolerated a significantly narrower range of speed deviations. In general, human observers are poor at judging the naturalness of speed in natural scenes except for events involving gravitational or biological motions.